Kompetensi Manajerial Kepala SMP Islam Al Azhar 15 Cilacap - Wardjono, Wardjono (Educreative : Jurnal Pendidikan Kreativitas Anak, 2020)
The problem in this research is the head of the school can manage all the components or resources that exist in the school environment with good so thatstudent achievement continues to rise in academic and non academic. The purpose of this study is: (1) Describe and analyze so that the head of school in implementing managerial competencies in SMP Islam Al Azhar 15 Cilacap. (2) Describe and analyze the response of the teachers and education personnel of the competence of the managerial head of school in SMP Islam Al Azhar 15 Cilacap. (3) Describe and analyze the contraints of the head of school in implementing mangerial competencies in SMP Islam Al Azhar 15 Cilacap. The results of this study are: (1) The head of the SMP Islam Al Azhar 15 Cilacap has been making efforts to utilize existing resources in the school environment both from human resources, school facilities and infrastructure, financial resources of the school, and the advancement of technology in the field of information and communication, which includes 16 type of competence; (2) support of personal is realized by setting up the school adminstration well in order to improve the quality of education, as for the support of educators is realized with: create lesson plans, implement learning process and assesment and evaluation; The head of SMP Islam Al Azhar 15 Cilacap get the constrains in implementing managerial competencies, namely limitations in manging the school’s finances.